2022
DOI: 10.1007/s40520-022-02238-1
|View full text |Cite
|
Sign up to set email alerts
|

The prevention of falls in patients with Parkinson’s disease with in-home monitoring using a wearable system: a pilot study protocol

Abstract: Background Parkinson's disease (PD) is a chronic, progressive neurodegenerative condition that gradually worsens motor function and leads to postural instability and, eventually, falls. Several factors may influence the frequency of future falls, such as slowness, freezing of gait, loss of balance, and mobility problems, cognitive impairments, and the number of previous falls. The TED bracelet is an advanced technological wearable device able to predict falls. Aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Based on this biobank initiative, disease-specific biobanking studies have already been published ( Table 1 ) [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ], and all the invited patients participating in these studies also adhered to the broader aims of the biobank by providing specific consent.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this biobank initiative, disease-specific biobanking studies have already been published ( Table 1 ) [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ], and all the invited patients participating in these studies also adhered to the broader aims of the biobank by providing specific consent.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies to date aimed at utilizing wearable sensors for fall risk prediction and monitoring in Parkinson's disease. [29][30][31][32] However, studies so far have failed to associate wearable sensors and bed alarms with a reduction in falls. 24,25,33 Moreover, a prospective study conducted in multiple nursing homes has shown that approximately 75% of falls occur in the residents' rooms and bathrooms.…”
Section: Discussionmentioning
confidence: 99%
“…The data used for the analysis were gathered during two similar studies [ 7 ], which required two slightly different, albeit equivalent, architectures. The shared components and the ones on which they differ are shown in Figure 1 and detailed below.…”
Section: System Architecturementioning
confidence: 99%
“…Furthermore, gait analysis provides insights into the functional decline associated with age-related musculoskeletal and neurological disorders. Conditions such as osteoarthritis, Parkinson’s disease, stroke, and peripheral neuropathy can significantly impact an individual’s gait pattern [ 7 ]. Continuous monitoring of gait parameters in these populations allows for the early detection of functional decline and facilitates the development of targeted interventions to mitigate the negative effects on mobility and overall quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation